Targeted analysis of 116 drugs in hair by UHPLC‐MS/MS and its application to forensic cases. Issue 8 (22nd December 2016) - Wang, Xin; Johansen, Sys Stybe; Nielsen, Marie Katrine Klose; Linnet, Kristian
Abstract : A multi‐target method that can detect a broad range of drugs in human hair, such as hypnotics, anxiolytics, analgesics, benzodiazepines, antihistamines, antidepressants, antipsychotics, and anticonvulsants, was developed based on ultra‐high‐performance liquid chromatography–tandem mass spectrometry (UHPLC‐MS/MS). The drugs were extracted from 10 mg of washed hair by incubation for 18 h in a 25:25:50 ( v/v/v ) mixture of methanol/acetonitrile/2 mM ammonium formate (8% acetonitrile, pH 5.3). For 51% of the basic drugs, the lower limits of quantification (LLOQs) were in the range of 0.05–0.5 pg/mg, and the majority (98%) were ≤ 5 pg/mg. Linearity ranged from LLOQs to 100–500 pg/mg for all the basic drugs. For acid and neutral drugs, the LLOQs ranged from 0.4 to 500 pg/mg, and linearity ranged from LLOQs to 80–40 000 pg/mg. According to published reports on concentrations attained in single dose control studies, the present method is sensitive enough to detect single‐dose drug exposure for many of the drugs. The accuracy was within 75–125% for the majority of drugs. Good precision was observed (relative standard deviations [RSD%] < 25%) for most of the compounds, including the prepared quality control (QC) hair samples. The method was applied to forensic cases and concentrations of rarely reported drugs in hair in 25 post‐mortem forensic cases were presented. Hair concentrations of amisulpride, gabapentin, mianserin, mepyramine, orphenadrine, and xylometazoline have not been previously reported. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A multi‐target method that can quantify a broad range of drugs and drugs of abuse (116 drugs) with high sensitivity in human hair using UHPLC–MS/MS was developed with a good performance in the validation. The applicability of the method was demonstrated by the analysis of forensic postmortem cases.